Compactness of the set of trajectories of the control system described by a Urysohn type integral equation with quadratic integral constraints on the control functions - Alias, Idham Arif; Huseyin, Nesir; Huseyin, Anar (SpringerOpen, 2016)
In this paper the control system is considered described by a Urysohn type integral equation which is nonlinear with respect to the state vector and is affine with respect to the control vector. The functions from the space L2([t0,θ];Rm) satisfying a quadratic integral constraint are chosen as admissible control functions. The set of trajectories generated by all admissible control functions is studied. The boundedness, closedness, precompactness, and hence the compactness of the set of trajectories in the space of continuous functions is proved.